Perancangan Termokopel Berbahan Besi (Fe) dan Tembaga (Cu) Untuk Sensor Temperatur - Andi Rosman N. (Universitas Negeri Makassar, 2018)
The design of iron (Fe) and Copper (Cu) thermocouples has been carried out for temperature sensors. The sensor will be made of two different types of materials namely iron and copper. The reference temperature used is 10C. The data collection procedure is first of all a thermocouple with a hot junction is tied together with a solder as a heat source. Besides that, it is also tied to a factory thermocouple that functions as a calibrator. Then the other end of the thermocouple (cold junction) will be inserted into a container containing ice cubes. Then the ports for each thermocouple will be connected to a multimeter, each of which is used to measure temperature (0C) and voltage (mV). From the results of observations and analyzes, it was found that for iron and copper thermocouples had the following characteristics: Seebeck coefficient was 0.001, the mean temperature rises and falls respectively (106.17 ± 0.82) 0C and (118.67 ± 0.90) 0C. The sensitivity of the thermocouple is 0.5 mV / 0C with linearity of 0.9.